Prognostic significances of PD-L1- and CTLA-4-positive T cells and positive correlations of immunosuppressive marker expression between cancer tissue and peripheral blood in patients with gastric cancer - Lee, Kun Hee; Kim, So Jung; Woo, Jin Seok; Lee, Seung Yoon; Jhun, Jooyeon; Moon, Jeonghyeon; Jung, Yoon Ju; Cho, Mi-La; Song, Kyo Young (Frontiers in Immunology, 2023)
Introduction Although tumor, node, metastasis (TNM) staging has been used for prognostic assessment of gastric cancer (GC), the prognosis may vary among patients with the same TNM stage. Recently, the TNM-Immune (TNM-I) classification staging system has been used for prognostic assessment of colorectal cancer based on intra-tumor T-cell status, which is a superior prognostic factor compared with the American Joint Committee on Cancer staging manual. However, an immunoscoring system with prognostic significance for GC has not been established. Method Here, we evaluated immune phenotypes in cancer and normal tissues, then examined correlations between tissues and peripheral blood. GC patients who underwent gastrectomy at Seoul St. Mary’s Hospital between February 2000 and May 2021 were included. We collected 43 peripheral blood samples preoperatively and a pair of gastric mucosal samples postoperatively, including normal and cancer mucosa, which did not influence tumor diagnosis and staging. Tissue microarray samples of GC were collected from 136 patients during surgery. We investigated correlations of immune phenotypes between tissues and peripheral blood using immunofluorescence imaging and flow cytometry, respectively. GC mucosa exhibited an increased number of CD4+ T cells, as well as increased expression levels of immunosuppressive markers (e.g., programmed death-ligand-1 [PD-L1], cytotoxic T lymphocyte antigen-4 [CTLA-4], and interleukin-10), in CD4+ T cells and non-T cells. Result The expression levels of immunosuppressive markers were significantly increased in cancer tissues and peripheral blood mononuclear cells. In gastric mucosal tissues and peripheral blood of GC patients, similar immunosuppression phenotypes were observed, including increased numbers of PD-L1- and CTLA-4-positive T cells. Discussion Therefore, peripheral blood analysis may be an important tool for prognostic assessment of GC patients.